To Tune or not to Tune? A Lightweight Physical Design Alerter - Chaudhuri, Surajit; Bruno, Nicolas (Proceedings of the International Conference on Very Large Databases (VLDB), 2006)
In recent years there has been considerable research on automating the physical design in database systems. Current techniques provide good recommendations, but are resource intensive. This makes DBAs somewhat conservative when deciding to launch a resource-intensive tuning session. In this paper, we introduce an alerter that helps determining when a physical design tool should be invoked. The alerter is a lightweight mechanism that provides guaranteed lower (and upper bounds) on the improvement that a DBA could expect by invoking a comprehensive physical design tool. Moreover, it produces an accompanying recommendation that serves as a “proof” for the lower bound. We show experimentally that the alerter handles large workloads with little overhead, and help judiciously decide on launching subsequent tuning sessions.